Physicomechanical properties of different nanohybrid composites after aging: color stability, flexural strength, and microhardness - Rafaella Caramori Saab; Adriana Osten Costacurta; Marina Samara Baechtold; Rafaella Ronchi Zinelli; Ana Beatriz Franco Fernandes; Gisele Maria Correr; Leonardo Fernandes da Cunha; Carla Castiglia Gonzaga (Universidade Estadual de Campinas, 2019)
Aim: To evaluate the physicomechanical properties of different hybrid composites (Charisma Diamond - CD, Aura - AU, NT Premium - NT, Opallis - OP, Filtek Z250 - Z250) after 6 months of aging in distilled water. Methods: Discs were fabricated and color measurements were performed after 24 hours and at 7, 30, and 180 days. Flexural strength was determined using the three-point bending test. For the microhardness test, the specimens were flattened to obtain polished and flat surfaces and indentations. The results for ∆E and microhardness were analyzed by two-way repeated-measures ANOVA and Tukey's HSD test. The flexural strength results were analyzed by two-way ANOVA and Tukey's test (α=0.05). Results: The ∆E values for composite resins varied in the following order: CD (3.54)a < Z250 (4.70)ab < AU (4.95)ab < OP (5.20)ab < NT (6.23)b. ∆E values were lower for 24 h (3.84)a < 7 days (4.43)ab < 30 days (4.93)b. The highest values were observed after 180 days (ΔE = 6.54)c. The flexural strength of composite resins varied in the following order: CD (89.17 MPa)a < Z250 (73.06 MPa)b < OP (60.30 MPa)c < NT (51.28 MPa)c < AU (23.77 MPa)d. Flexural strength values were significantly higher for 24 h (68.62 MPa)a < 180 days (51.40 MPa)b. The microhardness of composite resins varied in the following order: Z250 (112.05)a < CD (102.15)ab < OP (92.04)bc < NT (87.77)d < AU (87.68)d. Microhardness was significantly higher for 180 days (113.44)a < 24 h (78.21)b. Conclusion: The microhybrid (Z250) and one of the nanohybrid composites (CD) performed better. The color stability and flexural strength of all tested composites decreased with storage time.